Characterization of Kacang Goat skin Pepsin Soluble Collagen (Psc) and Their Potency as an Antioxidant (Jurnal Ilmu dan Teknologi Hasil Ternak, 2021)
Collagen have been interesting material for many utilization such as food, pharmaceutical and cosmetic in various products and target administration, consequently collagen should be prepared as well as type of application. The objective of this research is to prepare collagen from goat skin and investigate the character and their potency as an antioxidant. Kacang goat skin aged 2 years was used for collagen production. Small slice skin was extracted by curing with 0.1% (w/v) pepsin in acetic acid 0.5 M, for 24, 48, dan 72 h at 4°C. The variables observed were molecular weight by Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS PAGE), microstructure using scanning electron microscope, thermal stability by differential scanning calorimetric, and the antioxidant potency through 2,2-diphenyl-1-picrylhydrazyl (DPPH) inhibition analysis. The result showed the molecular weight range from 25 kDa to 180 kDa, microstructure showed the collagen fibril crosslink, collagen start to denature at 62,28°C, highest dissolved with 1% NaCl concentration and has highest DPPH inhibition at 60 min after hydrolysis. In conclusion, kacang goat skin collagen prepared by pepsin in acetic acid.